2018
DOI: 10.3390/app8112280
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acidic, Alkaline, and Neutral Anolytes on Electrochemical Seawater Deoxygenation

Abstract: Electrochemical deoxygenation of seawater has advantages over available chemical and physical methods. For seawater deoxygenation, acidic, neutral, or alkaline anolytes can be used. The effects of acidic, alkaline, and neutral buffered and non-buffered anolytes were studied in two compartment deoxygenation cells. The pH, conductivity, H2O2 production, and current were measured throughout the experiments. The optimum applied potentials for oxygen reduction were between 1.9 V–2.2 V, giving water as product; redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…6) must be higher than 357. Nickell et al [26] suggested the following equation to determine the activity of water in a concentrated NaOH solution: (7) where m is the molal concentration of NaOH, and T is the temperature in Kelvin. Based on this calculation, the water activity in a 50% w/w NaOH solution at 50 o C (i.e., a H2O(l) in Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6) must be higher than 357. Nickell et al [26] suggested the following equation to determine the activity of water in a concentrated NaOH solution: (7) where m is the molal concentration of NaOH, and T is the temperature in Kelvin. Based on this calculation, the water activity in a 50% w/w NaOH solution at 50 o C (i.e., a H2O(l) in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…As NaOH solutions are typically produced from sodium chloride (NaCl) solutions through a chloro-alkali process [4], the development of a process to selectively remove Cl¯ from the NaOH solutions is critical. Thus far, adsorption [5], precipitation [6], and electrodialysis [7] processes have been employed for this purpose. Commercially available 50% w/w NaOH solutions contain approximately 100 ppm Cl¯ (i.e., 100 mg Cl¯/kg NaOH).…”
Section: Introductionmentioning
confidence: 99%
“…Growing, the oxide islands interface between each other through a thin barrier layer, forcing the current to become localized in the gap of the joined protrusions. The rise of the electrolyte chemical activity nearby the anode [10] leads to the local dissolution of the oxide layer. Cavities, filled with the electrolyte, and transforming according to the oxide film growth into pores, are formed in the film.…”
Section: Resultsmentioning
confidence: 99%
“…[43] By separating the divalent anions and cations,t he formation of molecules that often cause scaling in BMED systems (e.g.,C aCO 3 and calcium sulfate (CaSO 4 )) can be prevented. [48] Furthermore,b ench-and pilot-scale [44,45] Fori nstance,c oating the surface of am embrane with polyethyleneimine improved the selectivity for monovalent cations over divalent cations while simultaneously increasing the overall water recovery after RO treatment.…”
Section: Selective Electrodialysismentioning
confidence: 90%